2022
DOI: 10.3390/gels8060340
|View full text |Cite
|
Sign up to set email alerts
|

Advanced CNC/PEG/PDMAA Semi-IPN Hydrogel for Drug Delivery Management in Wound Healing

Abstract: A Semi Interpenetrating Polymer Network (semi-IPN) hydrogel was prepared and loaded with an antibiotic drug, gentamicin, to investigate the wound healing activity of this system. The semi-IPN hydrogel was synthesized by combining natural polymer cellulose nanocrystal (CNC) and synthetic polymer polyethylene glycol (PEG) and poly (N,N′-dimethyl acrylamide) (PDMAA), which was initially added as a monomer dimethyl acrylamide (DMAA). CNC was prepared from locally obtained jute fibers, dispersed in a PEG-NaOH solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The bandage made from the formulation also showed a reduction in the amount of exudate as well as macrophage proliferation. Afrin et al [ 57 ] and Zhang et al [ 58 ] also confirmed the efficiency of hydrogels in the wound healing process in an in vivo study. The anti-inflammatory action observed in the results was attributed to flavonols (specifically rutin) present in the calendula extract.…”
Section: Resultsmentioning
confidence: 82%
“…The bandage made from the formulation also showed a reduction in the amount of exudate as well as macrophage proliferation. Afrin et al [ 57 ] and Zhang et al [ 58 ] also confirmed the efficiency of hydrogels in the wound healing process in an in vivo study. The anti-inflammatory action observed in the results was attributed to flavonols (specifically rutin) present in the calendula extract.…”
Section: Resultsmentioning
confidence: 82%
“…70,71 In addition, owing to their efficient delivery properties, hydrogels can be loaded with different active molecules, including drugs, cytokines, growth factors, and exogenous cells, such as stem cells and fibroblasts, to construct a delivery system suitable for different chronic wounds, promoting wound repair. 72,73 Classification and mechanism of multifunctional antibacterial hydrogels Universally, antibacterial properties arise from antibacterial hydrogel matrices and the release of antibacterial substances from composite hydrogels. Antibacterial hydrogels are classified into six categories based on their antibacterial mode: (1) hydrogels with inherent antibacterial activity, (2) biological extract-loaded hydrogels, (3) antibiotic-loaded hydrogels, (4) inorganic NP-loaded hydrogels, (5) carbon material-loaded hydrogels, and (6) stimulus-responsive hydrogels (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…These design are thermoplastic reinforcement, reinforcement based on inclusion of nanoparticles; reinforcement through energy dissipative networks such as supramolecular hydrogels, interpenetrating network or IPNs, Functionalization\dual crosslinking, supramolecular IPN, sliding crosslinking, functionalization nanocomposites, Nanocomposites IPNs, crosslinked microgels 181 . Example of usage of these networks in shape of hydrogels are CNC\PEG as nanocomposite hydrogel 175 , semi-IPN CNC/PEG/PDMAA hydrogel as IPN [182][183] , PVA/CNC-UPy supramolecular nanocomposite hydrogel 184 , hydroxypropyl-modified α-cyclodextrin (Hy-α-CD) and Acrylamide-PEG20000-Acrylamide as sliding movable crosslink supramolecular hydrogels 185 to just name a few. In randomly crosslinked hydrogels stress is concentrated; increasing crosslinking density leads to doubly crosslinked networks as the crosslinking links now acts as the second network.…”
Section: Physical or Chemical Networkmentioning
confidence: 99%